Pengaruh Peran TPPK, Pendidikan Orang Tua, dan Media Sosial Terhadap Bullying di Sekolah Dasar Se-Gugus Budi Wiyata 2 - Lilies Putri Rakhmawati; Rejokirono; Jumintono (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to examine: (1) the combined influence of the role of the School Violence Prevention and Handling Team (TPPK), parental education, and social media usage on bullying; (2) the influence of the TPPK's role on bullying; (3) the influence of parental education on bullying; and (4) the influence of social media on bullying in elementary schools within the Budi Wiyata 2 Cluster, North Magelang District. The research employed a quantitative approach using a survey method. Hypothesis testing was conducted through multiple linear regression analysis. The study population consisted of 566 parents of students from public elementary schools in the Budi Wiyata 2 Cluster, with a sample of 85 parents selected using Probability sampling. Data analysis was carried out using SPSS software, including prerequisite tests such as normality, linearity, and multicollinearity tests. Hypotheses were tested using multiple linear regression analysis, along with t-tests, F-tests, and the coefficient of determination (R²). The results showed that the variables of TPPK role, parental education, and social media significantly influenced bullying cases in public elementary schools within the Budi Wiyata 2 Cluster, North Magelang District, Magelang City.